Misrepresentations and misunderstandings in transport infrastructure planning: the case of corridor V in North-eastern Italy - Sandro Fabbro; Marco Dean (European Regional Science Association (ERSA), 2012)
The objective of the paper is to explore more realistic short-medium term national and regional strategies to reconnect local infrastructure systems to the wider networks through which global flows transit. As it is known, in the globalization era infrastructures depict the vital element for the functioning of the regional and urban complexes (Graham, 2010), allowing people, goods, energy, information and capitals to move about with unprecedented ease (Flyvbjerg et al., 2003; Rodrigue et al., 2009). At the same time, in this interconnected social and spatial networked system, infrastructures often bypass countries and regions which are less geographically favoured or not capable to adapt themselves to the changing logistic systems (Castells, 1997, Graham and Marvin, 2001). This aspect, together with the current economic crisis –characterized, particularly in the Eu, by strong cuts on public expenditure as well as on programs of public investment in infrastructures-, imposes, before undertaking new programs and projects, an accurate review of the old plans so as to determine whether the old provisions are still useful, effective and legitimate (Dimitriou, 2005). The paper argues that, until this moment, the Italian governments have not been able to adapt infrastructure and transport policies to the new transportation requirements. Policies and planning instruments which have been issued in Italy during the last decade have not been, in fact, selective concerning the identification of the priority infrastructures on which to place the few available resources and to promote private investment (Censis, 2009; Legambiente, 2011). In fact, the Italian governments, instead of basing their strategies on the most concrete TEN-T corridors connecting Italian ports with central Europe, have preferred to conceive their development programs on corridors, as the west-east Corridor V, having an uncertain horizon (Fabbro and Dean, 2012). As a consequence, instead of a favorable connection with the most productive areas of the Central Europe through the north-south Eu Corridors, Italy risks to be marginalized by the most significant global flows (Beretta et al., 2009; Confetra, 2011). In order to support this argumentation the authors present the case of the Region of Friuli Venezia Giulia, in the Nord-East of Italy where new regional plans are now finally rediscovering the north-south directrix -on the Adriatic-Baltic Corridor- instead of insisting on the less realistic Corridor V. According to the authors the case study provides evidence of the necessity of a drastic change in the national and regional short-medium term infrastructure strategies and relative planning.
Keywords: 330